The nature of Sk -67º 18 in the Large Magellanic Cloud: a multiple system with an O3f* component - Niemelä, Virpi Sinikka (2001)
We present the results of photometric and spectroscopic observations obtained between 1980 and 1996, which show that the bright star Sk-6718 in the Large Magellanic Cloud (LMC) is a multiple star which contains an eclipsing binary system. Our spectra show that this is an Of + O type binary, where the primary is probably of type O3f*. The orbital period of the eclipsing binary is almost exactly 2 days, which considerably compromises the obtaining of data with suitable phase coverage. Furthermore, from our radial velocity analysis of the spectral lines, Sk-6718 appears to be a multiple system consisting of at least two pairs of short-period binaries.